Negative active material and preparation method thereof, negative pole piece and battery

By embedding lithium lanthanum titanium oxide into the negative electrode active material of lithium-ion batteries, the problem of repeated growth of SEI film caused by high-silicon content materials during the lithium embedding process is solved, and the internal resistance of the battery is reduced and the cycle life is improved, meeting the needs of high-energy-density batteries.

CN119542376APending Publication Date: 2025-02-28SHENZHEN HIGHPOWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411486095.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The negative electrode active material with a silicon content exceeding 5 wt% leads to repeated growth of the SEI film during the lithium embedding process, increases the battery impedance, and leads to irreversible capacity loss.

Method used

By embedding lithium lanthanum titanium oxide (LLTO) into the pores of silicon-containing material with a three-dimensional porous structure, a tight interface contact is formed, which enhances the electronic conductance of silicon-containing material and lithium lanthanum titanium oxide, and buffers the volume expansion of silicon particles.

Benefits of technology

It reduces the internal resistance of the battery cell, reduces the repeated growth of the SEI film, improves the capacity and cycle life of the lithium-ion battery, and enables the negative electrode with higher silicon content to be used in the battery and improves the specific energy of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a negative electrode active material, the negative electrode active material comprises a silicon-containing material and lithium lanthanum titanium oxide, the silicon-containing material has a three-dimensional porous structure, the lithium lanthanum titanium oxide is embedded into pores of the silicon-containing material, the chemical formula of the lithium lanthanum titanium oxide is Li3xLa (2 / 3)-xTiO3, and the value range of X is 0 < x < (2 / 3); the lithium lanthanum titanium oxide is embedded into the pores of the silicon-containing material with the three-dimensional porous structure, the silicon-containing material and the lithium lanthanum titanium oxide form tight interface contact, a mixed ion electron conductor of the silicon-containing material and the lithium lanthanum titanium oxide can be formed when the battery is charged and lithium is embedded, and the electron conductivity of the silicon-containing material and the lithium lanthanum titanium oxide is enhanced; on one hand, the internal resistance of the battery cell is reduced, and on the other hand, the silicon-based material selectively adsorbs more LLTO and is embedded in the LLTO, so that the volume expansion of silicon particles is effectively buffered, the repeated growth of an SEI film is solved, the capacity exertion and cycle life of the lithium ion battery are improved, the negative electrode with higher silicon content is applied to the battery, and the specific energy of the battery is improved; and the requirements of the market on high-energy-density batteries are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material and a preparation method thereof, a negative electrode sheet and a battery. Background Art The traditional graphite anode cannot meet the practical application requirements of long-range new energy vehicles due to its limited energy density. Compared with the theoretical specific capacity of 372mAh / g of graphite anode, the lithium storage mechanism of silicon anode active material determines its theoretical specific capacity of up to 4200mAh / g, which has attracted extensive attention from researchers. In recent years, a composite material composed of a small amount of silicon (less than 5wt%) and graphite has been used as the anode of lithium-ion batteries. It not only retains the excellent conductivity and stable electrochemical properties of graphite, but also shows advantages such as high energy density. It has emerged in some high-specific energy and high-safety application fields (such as aerospace, electric vehicles and high-end communications). However, with the increase of silicon content, the anode active material forms alloys during the lithium insertion process, accompanied by a huge volume expansion effect. The volume expansion causes stress concentration inside the silicon particles, resulting in cracking to powdering, constantly exposing new surfaces, causing repeated growth of SEI film, and continuously consuming lithium ions in the electrolyte, resulting in irreversible capacity loss. The growing SEI film and byproducts hinder electron transfer and lithium ion diffusion, which is manifested as increased battery impedance. Therefore, negative electrode active materials with silicon content exceeding 5wt% are difficult to be industrially applied. Therefore, how to overcome the above-mentioned technical problems and defects becomes a key issue to be solved. Summary of the invention

[0002] In order to solve the problem that negative electrode active materials with a silicon content exceeding 5wt% will cause repeated growth of SEI film, resulting in increased battery impedance, the present invention provides a negative electrode active material and a preparation method thereof, a negative electrode plate and a battery.

[0003] The technical solution adopted by the present invention to solve the above technical problems is as follows: The first aspect of the present invention provides a negative electrode active material, the negative electrode active material comprises a silicon-containing material and lithium lanthanum titanium oxide, the silicon-containing material has a three-dimensional porous structure, the lithium lanthanum titanium oxide is embedded in the pores of the silicon-containing material, and the chemical formula of the lithium lanthanum titanium oxide is: Li 3x La (2 / 3)-x TiO3, wherein the value range of X is: 0<x<(2 / 3).

[0004] Optionally, the value range of X is: (1 / 24)≤x≤(1 / 6).

[0005] Optionally, based on the total weight of the negative electrode active material as 100%, the mass percentage of silicon in the silicon-containing material is 7.6%-8.6%, and the mass percentage of lithium lanthanum titanium oxide is 1%-3%.

[0006] Optionally, the silicon-containing material includes one or more of silicon elemental material, silicon-carbon material, and silicon-oxygen compound material.

[0007] Optionally, based on the total weight of the negative electrode active material being 100%, the mass percentage of the silicon-carbon material is 15%-25%; based on the total weight of the silicon-carbon material being 100%, the mass percentage of silicon in the silicon-carbon material is 37%-40%.

[0008] A method for preparing a negative electrode active material, comprising the following preparation method: S1. Obtaining a silicon-containing material having a three-dimensional porous structure; S2. The lithium lanthanum titanium oxide is mixed and dispersed with methanol to form a suspension, 2-vinyl pyridine is added to the suspension, and a polymerization reaction occurs to form a primary solution; S3. Dispersing the silicon-containing material having a three-dimensional porous structure in the primary solution, and adding ethylene glycol dimethacrylate and azobisisobutyronitrile to the primary solution, reacting in a vacuum environment, centrifuging and drying after the reaction, to obtain an imprinted porous silicon-containing material.

[0009] Optionally, in step S1, the method for preparing the silicon-containing material having a three-dimensional porous structure includes: S11. Prepare a mixed solution of AgNO3 and HF, take the silicon-containing material and add it to the mixed solution and stir; after washing, filtering and drying, a silicon-containing material having a surface modified with Ag particles is obtained; S12. Prepare a mixed solution of H2O2 and HF; add a silicon-containing material with Ag particles modified on the surface to the mixed solution, and after reaction, wash, filter and dry to obtain a silicon-containing material with a three-dimensional porous structure.

[0010] Optionally, in step S11, the concentration of AgNO3 in the mixed solution is 0.01 mol / L-0.02 mol / L, and the concentration of HF is 1 mol / L-5 mol / L.

[0011] Optionally, in step S12, the concentration of H2O2 in the mixed solution is 0.01mol / L-0.1mol / L, and the concentration of HF is 0.1mol / L-0.5mol / L.

[0012] Optionally, in step S11, the silicon-containing material needs to be pretreated, and the pretreatment process is: placing the silicon-containing material in ethanol and an aqueous solution for ultrasonic treatment respectively, and placing the filtered silicon-containing material in a vacuum drying oven for drying.

[0013] Optionally, in step 2, the mass ratio of the lithium lanthanum titanate to the 2-vinyl pyridine is 1:(1-3).

[0014] A second aspect of the present invention provides a negative electrode plate, comprising a current collector and a negative electrode material layer arranged on at least one surface of the current collector, the negative electrode material layer comprising a negative electrode material, a conductive agent and a binder, the negative electrode material comprising the negative electrode active material as described above or the negative electrode active material prepared by the negative electrode active material preparation method as described above.

[0015] A third aspect of the present invention provides a battery, comprising the negative electrode plate as described above.

[0016] According to the negative electrode active material provided by the present invention, lithium lanthanum titanate (LLTO) is embedded in the pores of the silicon-containing material with a three-dimensional porous structure, so that the silicon-containing material and the lithium lanthanum titanate form a close interface contact, and a mixed ionic electronic conductor of the silicon-containing material and the lithium lanthanum titanate can be formed when the battery is charged and lithium is inserted, thereby enhancing the electronic conductivity of the silicon-containing material and the lithium lanthanum titanate; on the one hand, the internal resistance of the battery cell is reduced, and on the other hand, since the silicon-based material selectively adsorbs more LLTO and embeds it therein, the volume expansion of the silicon particles can be effectively buffered, and the problem of repeated growth of the SEI film caused thereby can be solved, thereby improving the capacity and cycle life of the lithium-ion battery, so that the negative electrode with a higher silicon content can be used in the battery, thereby improving the specific energy of the battery and meeting the market demand for high energy density batteries. DETAILED DESCRIPTION

[0017] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0018] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0019] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0020] The first aspect of the present invention provides a negative electrode active material, the negative electrode active material comprises a silicon-containing material and lithium lanthanum titanium oxide, the silicon-containing material has a three-dimensional porous structure, the lithium lanthanum titanium oxide is embedded in the pores of the silicon-containing material, and the chemical formula of the lithium lanthanum titanium oxide is: Li 3x La (2 / 3)-x TiO3, where the value range of X is: 0<x<(2 / 3).

[0021] Specifically, the value range of X is: any point value among 0, 1 / 24, 1 / 12, 1 / 8, 1 / 6, 5 / 24, 1 / 4, 7 / 24, 1 / 3, 3 / 8, 5 / 12, 11 / 24, 1 / 2, 13 / 24, 7 / 12, 5 / 8 or 2 / 3, or a range of values ​​consisting of any two point values.

[0022] The present invention embeds lithium lanthanum titanate (LLTO) into the pores of a silicon-containing material with a three-dimensional porous structure, so that the silicon-containing material and the lithium lanthanum titanate form a close interface contact, and can form a mixed ion electronic conductor of the silicon-containing material and the lithium lanthanum titanate when the battery is charged and lithium is inserted, thereby enhancing the electronic conductivity of the silicon-containing material and the lithium lanthanum titanate; on the one hand, the internal resistance of the battery cell is reduced, and on the other hand, since the silicon-based material selectively adsorbs more LLTO and embeds it therein, the volume expansion of the silicon particles can be effectively buffered, and the problem of repeated growth of the SEI film caused thereby can be solved, thereby improving the capacity and cycle life of the lithium-ion battery, so that the negative electrode with a higher silicon content can be used in the battery, thereby improving the specific energy of the battery and meeting the market demand for high energy density batteries.

[0023] In a preferred embodiment, the value range of X is: (1 / 24)≤x≤(1 / 6).

[0024] When the value of X is in the range of (1 / 24)≤x≤(1 / 6), LLTO has a higher ionic conductivity (~10 -3 S / cm), a wide electrochemical window (~8V), a low conductivity activation energy (0.3-0.4eV), high temperature resistance (>1300℃) and excellent mechanical properties (Young's modulus>200GPa, Vickers hardness>9Gpa, flexural strength>239Mpa, fracture toughness>1Mpa, etc.).

[0025] In one embodiment, based on the total weight of the negative electrode active material being 100%, the mass percentage of silicon in the silicon-containing material is 7.6%-8.6%, and the mass percentage of lithium lanthanum titanium oxide is 1%-3%.

[0026] Specifically, the mass percentage of silicon in the silicon-containing material is any point value among 7.6%, 7.8%, 8.0%, 8.2%, 8.4% or 8.6%, or a range value consisting of any two point values; in a preferred embodiment, the mass percentage of silicon in the silicon-containing material is 8.0%.

[0027] Specifically, the mass percentage of lithium lanthanum titanium oxide is any point value of 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%, or a range value consisting of any two point values; in a preferred embodiment, the mass percentage of lithium lanthanum titanium oxide is 1.5%-2.5%.

[0028] When the mass percentage of silicon in the silicon-containing material is 7.6%-8.6%, it can form a close interface contact with lithium lanthanum titanium oxide, and can form a mixed ionic electronic conductor of the silicon-containing material and lithium lanthanum titanium oxide when the battery is charged and lithium is inserted, thereby enhancing the electronic conductivity of the silicon-containing material and lithium lanthanum titanium oxide, on the one hand reducing the internal resistance of the battery cell, and on the other hand buffering the volume change of silicon particles; when the mass percentage of the silicon-containing material is less than 7.6%, the capacity of the lithium-ion battery will be reduced, and it will be unable to meet the market demand for high energy density batteries; when the mass percentage of the silicon-containing material is greater than 8.6%, the cycle life of the lithium-ion battery will be shortened.

[0029] When the mass percentage of lithium lanthanum titanium oxide is 1%-3%, it can form a close interface contact with the silicon-containing material, and can form a mixed ion electronic conductor of the silicon-containing material and lithium lanthanum titanium oxide when the battery is charged and lithium is inserted, thereby enhancing the electronic conductivity of the silicon-containing material and lithium lanthanum titanium oxide, reducing the internal resistance of the battery cell on the one hand, and buffering the volume change of silicon particles on the other hand; when the mass percentage of lithium lanthanum titanium oxide is less than 1%, it will lead to the inability to form a uniform mixed ion electronic conductor, and cannot effectively reduce the internal resistance of the battery cell and buffer the volume change of silicon particles; when the mass percentage of lithium lanthanum titanium oxide is greater than 3%, the selective adsorption effect of the silicon-containing material will decrease, and the lithium lanthanum titanium oxide that is not selectively adsorbed will deteriorate the performance of the battery cell.

[0030] Specifically, the negative electrode active material further includes graphite, and the graphite includes at least one of artificial graphite and natural graphite, and the mass percentage of the graphite is 88% to 91% based on the mass of the negative electrode active material. By regulating the mass percentage of lithium lanthanum titanium oxide, the mass percentage of silicon-containing material and the mass percentage of graphite within the above range, the high surface stability of graphite can be used to protect the interface of silicon-containing material particles to a certain extent, thereby reducing the excessive generation of SEI film, thereby reducing the over-discharge gas generation voltage during the cycle of the secondary battery, and thus improving the safety performance and cycle performance of the secondary battery.

[0031] In one embodiment, the silicon-containing material includes one or more of silicon single substance material, silicon-carbon material, and silicon-oxygen compound material.

[0032] Specifically, the silicon single substance material includes one or more of nano silicon particles, silicon nanotubes, silicon nanowires, micro silicon particles and silicon thin films; Specifically, silicon-carbon materials include silicon-carbon alloys and silicon-carbon composite materials (materials formed by combining silicon with other carbon materials such as graphite, carbon nanotubes, carbon nanofibers, etc.).

[0033] Specifically, the silicon oxide compound material includes SiOx, wherein the value range of x is: 0<x≤2; In one embodiment, based on the total weight of the negative electrode active material being 100%, the mass percentage of the silicon-carbon material is 15%-25%; based on the total weight of the silicon-carbon material being 100%, the mass percentage of silicon in the silicon-carbon material is 37%-40%.

[0034] Specifically, the mass percentage of the silicon-carbon material is any point value among 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22, 23%, 24% or 25%, or a range value consisting of any two point values; in a preferred embodiment, the mass percentage of the silicon-carbon material is 18%-22%.

[0035] Specifically, the mass percentage of silicon in the silicon-carbon material is any point value of 37%, 37.5%, 38%, 38.5%, 39%, 39.5% or 40%, or a range value consisting of any two point values; in a preferred embodiment, the mass percentage of silicon in the silicon-carbon material is 38%-39%.

[0036] A method for preparing a negative electrode active material, comprising the following preparation method: S1. Obtaining a silicon-containing material having a three-dimensional porous structure; S2. The lithium lanthanum titanium oxide is mixed and dispersed with methanol to form a suspension, 2-vinyl pyridine is added to the suspension, and a polymerization reaction occurs to form a primary solution; S3. Dispersing the silicon-containing material having a three-dimensional porous structure in the primary solution, and adding ethylene glycol dimethacrylate and azobisisobutyronitrile to the primary solution, reacting in a vacuum environment, centrifuging and drying after the reaction, to obtain an imprinted porous silicon-containing material.

[0037] Specifically, in step S3, 100 mg of porous silicon powder is completely dispersed in the above primary solution, and then 150 uL (~0.8 mmol) of ethylene glycol dimethacrylate (EGDMA) and 20 mg of azobisisobutyronitrile (AIBN) are transferred to a centrifuge tube and mixed. All the liquid in the centrifuge tube is transferred to a 200 mL three-necked flask, and N2 is passed through an ice bath for deoxygenation for 20 minutes. After deoxygenation, the three-necked flask is sealed, magnetic stirring is performed at 800 r / min, oil bath heating is performed, prepolymerization is performed at 50 degrees Celsius for 1 hour, and reaction is performed at 60 degrees Celsius for 24 hours to obtain the desired suspension product. The product is centrifuged, the supernatant is discarded, methanol is added for repeated centrifugation, and sieving and filtering is performed. The product is vacuum dried at 45 degrees Celsius for 6 hours to finally obtain an imprinted porous silicon-containing material.

[0038] The present invention adopts the imprinting method of silicon-containing materials to prepare negative electrode active materials. Compared with non-imprinted silicon-containing materials, the distribution of LLTO can be effectively regulated after imprinting, and tends to be embedded in the surface of silicon-containing materials, especially under the condition of high silicon content and coexistence of other negative electrode active materials (graphite, hard carbon, soft carbon). A mixed ion electronic conductor is formed during the lithium insertion process, which enhances the electronic conductivity of the silicon-containing material, reduces the internal resistance of the battery cell, and buffers the volume expansion of the silicon-containing material, solves the problem of repeated growth of SEI film caused by this, and thus improves the capacity and cycle life of lithium-ion batteries. In this way, negative electrodes with higher silicon content can be used in batteries, thereby improving the specific energy of the battery and meeting the market demand for high energy density batteries.

[0039] In one embodiment, in step S1, the method for preparing a silicon-containing material having a three-dimensional porous structure includes: S11. Prepare a mixed solution of AgNO3 and HF, take the silicon-containing material and add it to the mixed solution and stir; after washing, filtering and drying, a silicon-containing material having a surface modified with Ag particles is obtained; S12. Prepare a mixed solution of H2O2 and HF; add a silicon-containing material with Ag particles modified on the surface to the mixed solution, and after reaction, wash, filter and dry to obtain a silicon-containing material with a three-dimensional porous structure.

[0040] Specifically, in step S11, a mixed solution of AgNO3 and HF is prepared, and a silicon-containing material is added to the mixed solution, and reacted for 5 minutes under rapid stirring; then, the mixed solution is washed with deionized water several times and filtered, and then dried in a vacuum oven to obtain a silicon-containing material with Ag particles modified on the surface; In step S12, a mixed solution of H2O2 and HF is prepared; a silicon-containing material with Ag particles modified on the surface is added to the mixed solution, reacted for 30 minutes, washed with deionized water for multiple times, filtered, and dried to obtain a silicon-containing material with a three-dimensional porous structure.

[0041] Specifically, the silicon-containing material having a three-dimensional porous structure facilitates the embedding of lithium lanthanum titanium oxide into its surface, thereby enhancing the electronic conductivity of the silicon-containing material.

[0042] In one embodiment, in step S11, the concentration of AgNO 3 in the mixed solution of AgNO 3 and HF is 0.01 mol / L-0.02 mol / L, and the concentration of HF is 1 mol / L-5 mol / L.

[0043] Specifically, the concentration of AgNO3 is any one of 0.01mol / L, 0.011mol / L, 0.012mol / L, 0.013mol / L, 0.014mol / L, 0.015mol / L, 0.016mol / L, 0.017mol / L, 0.018mol / L, 0.019mol / L or 0.02mol / L, or a range value consisting of any two of the concentration values.

[0044] In a preferred embodiment, the concentration of AgNO3 is 0.015 mol / L.

[0045] Specifically, the concentration of HF is any one of 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L or 5 mol / L, or a range consisting of any two of the concentration values.

[0046] In a preferred embodiment, the concentration of HF is 2 mol / L.

[0047] In one embodiment, in step S12, the concentration of H2O2 in the mixed solution of H2O2 and HF is 0.01 mol / L-0.1 mol / L, and the concentration of HF is 0.1 mol / L-0.5 mol / L.

[0048] Specifically, the concentration of H2O2 is any one of 0.01mol / L, 0.02mol / L, 0.03mol / L, 0.04mol / L, 0.05mol / L, 0.06mol / L, 0.07mol / L, 0.08mol / L, 0.09mol / L or 0.1mol / L, or a range value consisting of any two of the concentration values.

[0049] In a preferred embodiment, the concentration of H2O2 is 0.05 mol / L.

[0050] Specifically, the concentration of HF is any one of 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L or 0.5 mol / L, or a range consisting of any two of the concentration values.

[0051] In a preferred embodiment, the concentration of HF is 0.15 mol / L.

[0052] In one embodiment, in step S11, the silicon-containing material needs to be pretreated, and the pretreatment process is: placing the silicon-containing material in ethanol and an aqueous solution for ultrasonic treatment respectively, and placing the filtered silicon-containing material in a vacuum drying oven for drying.

[0053] The pretreatment process of silicon-containing materials can reduce impurities attached to the surface of the silicon-containing materials and reduce other unnecessary products produced by subsequent chemical reactions.

[0054] In one embodiment, in step 2, the mass ratio of lithium lanthanum titanate to 2-vinyl pyridine is 1:(1-3).

[0055] Specifically, in step 2, 20 mg of LLTO template molecules were weighed and placed in a 100 mL centrifuge tube, 80 mL of methanol was added, and ultrasonic dispersion was performed, and 0.4 mmol of 2-vinylpyridine (VPY) was added to the suspension and prepolymerized by ultrasonication.

[0056] Specifically, the mass ratio of lithium lanthanum titanate to 2-vinyl pyridine is any one of 1:1, 1:1.5, 1:2, 1:2.5, and 1:3, or a range consisting of any two of the concentration values.

[0057] In a preferred embodiment, the mass ratio of lithium lanthanum titanate to 2-vinyl pyridine is 1:2.

[0058] A second aspect of the present invention provides a negative electrode plate, including a current collector and a negative electrode material layer arranged on at least one surface of the current collector, the negative electrode material layer includes a negative electrode material, a conductive agent and a binder, and the negative electrode material includes the negative electrode active material as described above or the negative electrode active material prepared by the negative electrode active material preparation method described above.

[0059] Specifically, the negative electrode material also includes a binder and a conductive agent, the binder includes one or more of lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, styrene-butadiene rubber, styrene acrylic emulsion, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, lithium alginate, sodium alginate or potassium alginate, and the conductive agent includes one or more of amorphous carbon, SuperP, Ketjen black, acetylene black, carbon nanotubes, carbon nanofibers and graphene.

[0060] Taking the total weight of the negative electrode material layer of the negative electrode sheet as 100%, the mass percentage of the binder is 4.0%-4.9%, and the mass percentage of the conductive agent is 0.1%-1.0%.

[0061] In some embodiments, the negative electrode plate further includes a negative electrode current collector, and the negative electrode material layer covers the surface of the negative electrode current collector. In the present application, all parts of the negative electrode except the negative electrode current collector are referred to as the negative electrode material layer.

[0062] The negative electrode current collector is selected from metal materials that can conduct electrons. Preferably, the negative electrode current collector includes metals such as stainless steel, Al, Ni, tin, copper, nickel, titanium, iron, or their alloys. In a more preferred embodiment, the negative electrode current collector is selected from copper foil.

[0063] A third aspect of the present invention provides a battery, comprising the negative electrode plate as described above.

[0064] The battery provided by the present invention is a lithium ion battery. The battery of the present invention also includes a positive electrode sheet and a separator. The positive electrode sheet generally includes a positive current collector and a positive active material layer located on the surface of the positive current collector. The positive active material layer generally includes a positive active material. The positive active material can be various positive active materials suitable for secondary batteries in the art. For example, the positive active material can be, but is not limited to, lithium transition metal composite oxides, etc. More specifically, the lithium transition metal composite oxide can be, but is not limited to, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or compounds obtained by adding other transition metals or non-transition metals to these lithium transition metal oxides, including lithium cobalt oxide, lithium nickel cobalt manganese oxide, nickel cobalt aluminum, lithium-rich manganese-based, etc. One or more combinations of the like. The positive current collector can be a material such as a metal foil or a porous metal plate. For example, the metal suitable for the positive current collector can be a metal such as copper, aluminum, or an alloy thereof.

[0065] In some embodiments, the positive electrode active material layer may further include a binder. As non-limiting examples, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0066] In some embodiments, the positive electrode active material layer may further include a conductive agent. As non-limiting examples, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0067] In the secondary battery provided by the present invention, the separator can be various separator materials suitable for lithium-ion batteries in the art, for example, it can be a combination of one or more of including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber.

[0068] In the secondary battery provided by the present invention, the positive electrode sheet, the separator and the negative electrode sheet can generally be used to form a battery cell of a lithium-ion battery. For example, the positive electrode sheet, the separator and the negative electrode sheet can each be a layer body, so that they can be cut into a target size and stacked in sequence, and can be further combined with an electrolyte to form a lithium-ion battery. The positive electrode sheet, the separator and the negative electrode sheet can directly form a single-layer laminated battery, and can also be further wound to a target size to form a battery cell, and can be further combined with an electrolyte to form a lithium-ion battery. However, in a preferred embodiment of the present invention, the lithium-ion battery is a single-layer laminated battery. Such a battery is easier to operate during the floating charge process on the one hand, and has a lower screening cost on the other hand. The lithium-ion battery can also include various other components that can be used for lithium-ion batteries. For example, applicable components can include but are not limited to packaging shells, pole ears, external electrodes, etc.

[0069] Typically, secondary batteries also include an electrolyte. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The diaphragm is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0070] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0071] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0072] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0073] In some of the embodiments, the solvent may include one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate, fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0074] The preparation method and application of the present invention will be further described in detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0075] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0076] Table 1 Parameter design of negative electrode material in embodiments and comparative examples: Table 1 Note: Examples 1-7 and Comparative Example 1 use lithium cobalt oxide (LCO) as the positive electrode material, and Example 8 and Comparative Example 2 use lithium iron phosphate (LFP) as the positive electrode material.

[0077] Example 1: 4.5V Li-ion Battery This embodiment is used to illustrate the negative electrode active material, negative electrode plate and battery disclosed in the present invention, and includes the following operating steps: Preparation method of negative electrode sheet: Silicon carbon, graphite, LLTO (Li 0.33 La 0.56 TiO3) was put into a ball mill for premixing for 10 minutes, and then polyacrylic acid, water and carbon nanotubes were added respectively and mixed at 1500rpm for 30 minutes. Finally, styrene-butadiene rubber latex (SBR) was added and stirred at 600rpm for 8 minutes until the slurry had good fluidity and no granularity (the weight ratio of silicon: graphite: LLTO: PAASBR: CNT was 19.17: 73.68: 3.00: 2.70: 1.30: 0.15), and the desired negative electrode sheet was obtained by coating and baking.

[0078] Preparation method of positive electrode sheet: Lithium cobalt oxide electrode: Mix polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) at 500 rpm for 5 minutes, then add lithium cobalt oxide positive electrode material (LCO, with a withstand voltage below 4.53V) and carbon black (CB) and blend at 1000 rpm for 20 minutes until the slurry has good fluidity and no granularity (the weight ratio of LCO: PVDF: CB is 96:3:1, and the solid content is 45%). Apply and bake to obtain the required positive electrode.

[0079] Preparation of diaphragm: A 12 μm PP porous membrane was used as the separator.

[0080] Preparation of lithium-ion batteries: The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound up, and the electrode assembly is packed into an aluminum-plastic film packaging bag, and the top and side are sealed to obtain a soft-pack battery with a designed capacity of 5Ah; commercially available electrolyte is injected, and the bag is sealed and left to stand after evacuation; after formation, a lithium-ion battery A is obtained.

[0081] Embodiments 2 to 8 Examples 2 to 8 are used to illustrate the negative electrode active material, negative electrode plate and battery disclosed in the present invention, and include most of the operating steps in Example 1, except that: The types and contents of the negative electrode active materials used in Examples 2 to 8 are shown in Table 1.

[0082] In Example 8, lithium iron phosphate is used as the positive electrode sheet, and the preparation method is similar to that of the lithium cobalt oxide electrode sheet in Example 1, except that lithium iron phosphate positive electrode material (LFP) is added.

[0083] Comparative Example 1-2 Comparative Examples 1-2 are used to compare and illustrate the negative electrode active material, negative electrode plate and battery disclosed in the present invention, and include most of the operating steps in Example 1, except that: The types and contents of the negative electrode active materials used in Comparative Examples 1-2 are shown in Table 1; And comparative example 2 uses lithium iron phosphate as the positive electrode.

[0084] Performance Test: The lithium-ion battery prepared above was subjected to the following performance tests: 1. Internal resistance test: The AJ internal resistance of the battery before the cycle is made is recorded by an internal resistance tester; 2. Cycle performance test: The test temperature is 25°C (±5°C). The batteries prepared by Examples 1-7 and Comparative Example 1 are charged to 4.5V at 0.5C constant current and constant voltage, cut off at 0.02C, and discharged to 2.75V at 0.5C after standing for 30 minutes. The capacity obtained in this step is taken as the initial capacity. After that, a cycle test is performed. The capacity of each step is compared with the initial capacity to obtain a capacity decay curve. The batteries prepared by Example 8 and Comparative Example 2 are charged to 3.65V at 0.5C constant current and constant voltage, cut off at 0.02C, and discharged to 2.5V at 0.5C after standing for 30 minutes. The capacity obtained in this step is taken as the initial capacity. After that, a cycle test is performed. The capacity of each step is compared with the initial capacity to obtain a capacity decay curve. The number of cycles at which the capacity retention rate at 25°C is 90% is recorded as the room temperature cycle performance of the battery.

[0085] The results are shown in Table 2.

[0086] Table 2 Test results obtained from Examples 1 to 8 and Comparative Examples 1-2 It can be seen from the parameters in Table 1 and the test results in Table 2 that, by comparing Examples 1-8 with Comparative Examples 1-2, when lithium lanthanum titanium oxide is added to the negative electrode active material, the internal resistance of the battery cell can be reduced and the cycle life of the battery can be increased. In Examples 1-8 of the present invention, adding lithium lanthanum titanium oxide to the negative electrode active material can reduce the internal resistance of the battery cell and increase the cycle life of the battery, so that the battery has better long cycle performance.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode active material, characterized in that: The negative electrode active material comprises a silicon-containing material and lithium lanthanum titanate, wherein the silicon-containing material has a three-dimensional porous structure, and the lithium lanthanum titanate is embedded in the pores of the silicon-containing material. The chemical formula of the lithium lanthanum titanate is: Li 3x La (2 / 3)-x TiO3, wherein the value range of X is: 0<x<(2 / 3).

2. The negative electrode active material according to claim 1, characterized in that: The value range of X is: (1 / 24)≤x≤(1 / 6).

3. The negative electrode active material according to claim 1, characterized in that: Taking the total weight of the negative electrode active material as 100%, the mass percentage of silicon in the silicon-containing material is 7.6%-8.6%, and the mass percentage of lithium lanthanum titanium oxide is 1%-3%.

4. The negative electrode active material according to claim 1, characterized in that: The silicon-containing material includes one or more of silicon single substance material, silicon-carbon material, and silicon-oxygen compound material.

5. The negative electrode active material according to claim 4, characterized in that: Taking the total weight of the negative electrode active material as 100%, the mass percentage of the silicon-carbon material is 15%-25%; taking the total weight of the silicon-carbon material as 100%, the mass percentage of silicon in the silicon-carbon material is 37%-40%.

6. A method for preparing a negative electrode active material according to any one of claims 1 to 5, characterized in that: The invention comprises the following preparation methods: S1. Obtaining a silicon-containing material having a three-dimensional porous structure; S2. The lithium lanthanum titanium oxide is mixed and dispersed with methanol to form a suspension, 2-vinyl pyridine is added to the suspension, and a polymerization reaction occurs to form a primary solution; S3. Dispersing the silicon-containing material having a three-dimensional porous structure in the primary solution, and adding ethylene glycol dimethacrylate and azobisisobutyronitrile to the primary solution, reacting in a vacuum environment, centrifuging and drying after the reaction, to obtain an imprinted porous silicon-containing material.

7. The method for preparing the negative electrode active material according to claim 6, characterized in that: In step S1, the method for preparing the silicon-containing material having a three-dimensional porous structure includes: S11. Prepare a mixed solution of AgNO3 and HF, take the silicon-containing material and add it to the mixed solution and stir; after washing, filtering and drying, a silicon-containing material having a surface modified with Ag particles is obtained; S12. Prepare a mixed solution of H2O2 and HF; add a silicon-containing material with Ag particles modified on the surface to the mixed solution, and after reaction, wash, filter and dry to obtain a silicon-containing material with a three-dimensional porous structure.

8. The method for preparing the negative electrode active material according to claim 7, characterized in that: In the step S11, the concentration of AgNO3 in the mixed solution is 0.01mol / L-0.02mol / L, and the concentration of HF is 1mol / L-5mol / L.

9. The method for preparing the negative electrode active material according to claim 7, characterized in that: In the step S12, the concentration of H2O2 in the mixed solution is 0.01 mol / L-0.1 mol / L, and the concentration of HF is 0.1 mol / L-0.5 mol / L.

10. The method for preparing the negative electrode active material according to claim 7, characterized in that: In the step S11, the silicon-containing material needs to be pretreated, and the pretreatment process is: placing the silicon-containing material in ethanol and an aqueous solution for ultrasonic treatment respectively, and placing the filtered silicon-containing material in a vacuum drying oven for drying.

11. The method for preparing the negative electrode active material according to claim 6, characterized in that: In the step 2, the mass ratio of the lithium lanthanum titanate to the 2-vinyl pyridine is 1:(1-3).

12. A negative electrode plate, characterized in that: It includes a current collector and a negative electrode material layer arranged on at least one surface of the current collector, the negative electrode material layer includes a negative electrode material, a conductive agent and a binder, and the negative electrode material includes the negative electrode active material as described in any one of claims 1 to 5 or the negative electrode active material prepared by the preparation method of the negative electrode active material as described in any one of claims 6 to 11.

13. A battery, characterized in that: Comprising the negative electrode sheet as described in claim 12.